The Relationship Between Sodium (Na⁺), Potassium (K⁺), and Chloride (Cl⁻) Electrolyte Disorders and Clinical Conditions in Elderly Patients in the Emergency Room of Yarsi Hospital for the Period January to December 2023 - Mirshanti Muthia Khaliza; Syukrini Bahri; Afrizal Tw; Endah Purnamasari (Green Publisher Indonesia, 2026)
Elderly patients are prone to electrolyte balance disorders due to aging, decreased organ function, hormonal changes, and high comorbidities. Imbalances of sodium, potassium, and chloride can affect neurological, muscle, and cardiovascular function, thus contributing to clinical instability in the emergency room. This study is an observational study of cross-cutting design analysis based on secondary data of medical records. The subject is an elderly patient (≥60 years old) who underwent an electrolyte examination at the Yarsi Hospital Emergency Room for the January-December 2023 period. Of the 1,730 visits, 315 patients met the inclusion criteria. The variables analyzed included sodium, potassium, chloride levels, as well as characteristics of age, sex, and clinical condition upon admission. Univariate and bivariate analysis was performed using the Chi-Square test. The majority of subjects were early elderly women. Hyponatremia is the most frequent disorder, followed by hypokalemia and hypochloremia. A total of 53% of patients experienced one electrolyte disorder, 36.2% two disorders, and 10.8% three disorders at once. The most common clinical conditions are low intake, chronic kidney disease, diabetes mellitus, infection, CVDNH, and vomiting. The Chi-Square test showed a significant association between clinical conditions and sodium (p=0.029), potassium (p=0.038), and chloride (p=0.027) impairments. Electrolyte disorders in the elderly in the emergency room are significantly related to the patient's clinical condition. Hyponatremia is most dominant and is associated with poor intake, chronic kidney disease, infections, and diabetes.